Age‐ and Lesion‐Related Comorbidity Burden Among US Adults With Congenital Heart Disease: A Population‐Based Study. Issue 20 (15th October 2019) - Agarwal, Anushree; Thombley, Robert; Broberg, Craig S.; Harris, Ian S.; Foster, Elyse; Mahadevan, Vaikom S.; John, Anitha; Vittinghoff, Eric; Marcus, Greg M.; Dudley, R. Adams
Abstract : Background: As patients with congenital heart disease (CHD) are living longer, understanding the comorbidities they develop as they age is increasingly important. However, there are no published population‐based estimates of the comorbidity burden among the US adult patients with CHD. Methods and Results: Using the IBM MarketScan commercial claims database from 2010 to 2016, we identified adults aged ≥18 years with CHD and 2 full years of continuous enrollment. These were frequency matched with adults without CHD within categories jointly defined by age, sex, and dates of enrollment in the database. A total of 40 127 patients with CHD met the inclusion criteria (mean [SD] age, 36.8 [14.6] years; and 48.2% were women). Adults with CHD were nearly twice as likely to have any comorbidity than those without CHD ( P <0.001). After adjusting for covariates, patients with CHD had a higher prevalence risk ratio for "previously recognized to be common in CHD" (risk ratio, 9.41; 95% CI, 7.99–11.1), "other cardiovascular" (risk ratio, 1.73; 95% CI, 1.66–1.80), and "noncardiovascular" (risk ratio, 1.47; 95% CI, 1.41–1.52) comorbidities. After adjusting for covariates and considering interaction with age, patients with severe CHD had higher risks of previously recognized to be common in CHD and lower risks of other cardiovascular comorbidities than age‐stratified patients with nonsevere CHD. For noncardiovascular comorbidities, the risk was higher among patients with severe than nonsevere CHD before, but not after, the age of 40 years. Conclusions: Our data underscore the unique clinical needs of adults with CHD compared with their peers. Clinicians caring for CHD may want to use a multidisciplinary approach, including building close collaborations with internists and specialists, to help provide appropriate care for the highly prevalent noncardiovascular comorbidities.